Transdisciplinární didaktika: o učitelském sdílení znalostí a zvyšování kvality výuky napříč obory - Slavík, Jan (Syntézy výzkumu vzdělávání, 2017)
Title in English: Transdisciplinary didactics: on teachers' knowledge sharing and improving teaching in different subjects. The book concentrates on teaching and instructional quality with emphasis on the relationship between educational theory and practice with respect to teacher education. In the first part of the book, philosophical and theoretical background is introduced of a research specific methodology that focuses on analysing the development of instructional environment and also on assessing its quality. In the second part of the book, the 3A procedure is described as a research approach specifically designed to analyse instructional quality. The third part of the book summarises the results of a multicase study carried out within the framework of the 3A procedure. The book aims to serve as inspiration to theorists in general and field didactics, teachers interested in instructional quality, school headmasters and all those who assess the didactical quality of instruction.